Hyperreality and Reality: Contestation of PT Dewandra Corporate Narratives and the Alam Permai Village Community - Kiki Amelia Sari; Waskito (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2024)
This study aims to examine hyperreality and reality between the corporate narrative of PT Dewandra and the community of Alam Permai Village, an area in East Java, using Jean Baudrillard's Hyperreality theory. To achieve this goal, the researcher used a qualitative approach with a phenomenological research design. The subjects in this study were those who were pro PT Dewandra (Head of Alam Permai Village and those who were anti PT Dewandra) and those who were anti PT Dewandra (Social activists, community lawyers and people who were against PT Dewandra). The selection of research subjects was carried out using the snowball sampling technique. The researcher used data collection techniques through participant observation, indepth interviews, literature studies and documentation. The data obtained were analyzed through data condensation, data presentation, and drawing conclusions. The results of the study indicate that the narrative of the PT Dewandra Indonesia company profile is a form of simulacra that gives rise to hyperreality in society. On the other hand, the community narrative reflects both positive and negative realities regarding the existence of PT Dewandra for the local community and environment.The results of this study are expected to provide benefits for all stakeholders who support large company investments in the community so that various negative impacts from the company are not experienced by the community.